Analyzing the Participation Factors of Local Labour in the Malaysian Construction Industry - Mohd Najib, Iskandar Zulkarnain; Mohd Nordin, Rumaizah; Ismail, Zulhabri (International Journal of Sustainable Construction Engineering and Technology, 2020)
The dependency of the Malaysian construction industry on foreign workers affected the productivity of the industry. Sustainable supply of sufficient talent is required in order for Malaysia to support the aim that had been targeted under CITP, where productivity is one of the thrusts in the transformation program for the industry. However, the hardship in the recruitment of local talent has worsened the scenario and caused the industry player to prefer hiring foreign workers compared to local labour. Thus, the aim of the study is to analyse the participation factors of local labour in the Malaysian construction industry. This paper presents a survey result of 45 respondents which involves the industry player around Petaling District in Selangor. The findings from this research summarise the participation factor of local labour in the Malaysian construction industry. It is hoped that the findings of this study may assist in stimulating the number of local labours in the construction industry through better productivity among the construction stakeholders especially the contractors in conjunction with the CITP strategic thrust.